Dimensions of Cognitive Processes and Dimensions of Knowledge in School Exam Questions for Junior High School Mathematics in Subrayon 05, Semarang Regency - Enika Wulandari; Muhammad Afif; Nisa Fitriana (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
This study aims to describe the cognitive processes and knowledge dimensions that are measured on exam questions for junior high school mathematics in the Subrayon 05 Semarang Regency for the 2021/2022 academic year. This study uses a qualitative approach with content analysis techniques. Data collection is carried out through documentation. For further analysis of the contents of the data in the form of school exam questions. The research instrument includes a question review guide that is determined based on the dimensions of cognitive processes and the dimensions of knowledge. The results showed that the dimensions of cognitive processes and the dimensions of students' knowledge as measured through school exam questions for Mathematics subjects in Sub-Rayon 05 Semarang Regency ranged from understanding facts to creating which procedures; on questions that measure understanding facts, students are asked to classify facts in the form of notation, on questions that measure understanding of concepts, students are asked to classify related to certain mathematical concepts; on questions that measure applying concepts, students are asked to use or implement certain mathematical concepts in order to solve problems; on questions that measure applying procedures, students are asked to use or carry out certain mathematical procedures in order to solve problems; In questions that measure the ability to create procedures, students are asked to generate/hypothesizing specific skills and algorithms.